2022
DOI: 10.1111/ajt.16996
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of liver transplantation with grafts from brain-dead donors treated with dual hypothermic oxygenated machine perfusion, with particular reference to elderly donors

Abstract: Prompted by the utilization of extended criteria donors, dual hypothermic oxygenated machine perfusion (D‐HOPE) was introduced in liver transplantation to improve preservation. When donors after neurological determination of death (DBD) are used, D‐HOPE effect on graft outcomes is unclear. To assess D‐HOPE value in this setting and to identify ideal scenarios for its use, data on primary adult liver transplant recipients from January 2014 to April 2021 were analyzed using inverse probability of treatment weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 65 publications
5
61
1
Order By: Relevance
“…Patrono et al demonstrated a reduction in major complications including the severity of NAS after D-HOPE treatment in more than 100 perfused grafts. The findings were confirmed in a subset of transplantations from old DBD donors 42 . Overall, there is increasing evidence that a simple endischemic HOPE-treatment is effective in the reduction of biliary complications in various grafts types, including DCD livers and other extended criteria donor grafts.…”
Section: Hope Protects From Biliary Complicationssupporting
confidence: 53%
“…Patrono et al demonstrated a reduction in major complications including the severity of NAS after D-HOPE treatment in more than 100 perfused grafts. The findings were confirmed in a subset of transplantations from old DBD donors 42 . Overall, there is increasing evidence that a simple endischemic HOPE-treatment is effective in the reduction of biliary complications in various grafts types, including DCD livers and other extended criteria donor grafts.…”
Section: Hope Protects From Biliary Complicationssupporting
confidence: 53%
“…In the first clinical series published by Guarrera et al [ 23 ] transaminase peak after liver transplant positively correlated with transaminase and LDH levels in perfusate, with however limited impact on the clinical outcome and complications. Among different perfusion parameters, Patrono et al [ 54 ] found that ALT level at 90 min was the best predictor of EAD with a cutoff of 537 IU/L, although this result was not confirmed at multivariate analysis. Moreover, 90 min LDH had the highest correlation with the liver graft assessment following transplantation (L-GrAFT) risk score [ 55 ].…”
Section: Viability Parameters During Hmpmentioning
confidence: 97%
“…Related to this reduced inflammation, the HOPE procedure further diminishes later biliary complications based on a lower release of profibrotic molecules from stellate cells and myofibroblasts after LT [ 111 , 112 ]. Whilst these findings were mainly explored in experimental and clinical studies with DCD livers, there is also some evidence in DBD grafts from elderly donors and in fatty livers, where HOPE was found to reduce IRI with subsequent improved early function and graft survival [ 67 , 113 , 114 ].…”
Section: Strategies With the Potential To Reduce Cancer Recurrencementioning
confidence: 99%
“…The impact of HOPE on clinical results was investigated in many studies, which consistently show the protective effects, with reduced IRI, less bile duct injury, and better graft function, with a follow-up of up to 5 years [ 107 , 114 , 115 , 116 , 117 , 118 ]. Additional evidence comes from three RCTs, which confirmed the HOPE effect, with protection from post-transplant biliary complications, EAD, high peak transaminases, and better graft survival rates in various graft types, including DCD livers [ 119 , 120 , 121 ].…”
Section: Strategies With the Potential To Reduce Cancer Recurrencementioning
confidence: 99%